Leading By Example: A Three-Wave Sequential Mixed Method Food Safety Study Item - Lin, Naiqing (My University, 2020)
Foodservice employees that fail to adhere to food safety practices may directly introduce pathogens that can cause illness and death. Therefore, the purpose of this study was to explore managerial practices that influence employee’s food safety behaviors, using a two-phase sequential mixed-method approach. A total of 642 foodservice employees currently working in the United States participated in a survey about food safety knowledge and food safety behavioral intentions. Among these, 263 were invited to answer a set of open-ended qualitative questions, 36 participants responded to the questions, and two participants were selected for in-depth interviews. The majority of the employees are optimistic about their daily food safety practices. However, cross-analyses noted that the majority of employees failed the quiz regarding basic food safety knowledge. Further analyses documented that time-constraint and lack of managerial role modeling in daily food safety practices can post a considerable threat to maintaining food safety behaviors.
Keywords: food safety behavior; food safety interviews; behavioral intentions; managerial practices; Nest-purposeful sampling; Heuristic narratives